Three-dimensional self-supported iron-doped nickel sulfides for sustainable overall water splitting. (November 2020) - Zhang, Changqin; Zhou, Shuai; Dong, Xiaojun; Han, Yue; Li, Jiahui; Yin, Wenzheng
Abstract: In this short communication, a three-dimensional (3D) iron-doped nickel sulfides catalyst supported was successfully prepared on commercial Ni–Fe foam through one-step heat sulfurization, and its electrocatalytic performance for water splitting in 1 M KOH was investigated. In a symmetric two-electrode system assembled by the prepared electrocatalyst, an ultralow cell voltage of 1.46 V was required to drive 10 mA cm −2, which was much lower than that of the symmetric two-electrode system assembled by bare Ni foam, bare Ni–Fe foam, or nickel sulfides without iron doping. The iron-doped nickel sulfides had desirable stability for overall water splitting, and the electrocatalytic performance showed no significant degradation during long-term durability test (70 h at 10 mA cm −2 ). The 3D porous structure of Ni–Fe foam, the in-situ growth of catalyst, and the combined iron doping effects contributed to the outstanding performance of our prepared catalyst for overall water splitting. Highlights: Iron-doping nickel sulfides supported on Ni–Fe foam are prepared through heat sulfurization under argon atmosphere. A cell voltage of only 1.46 V is required to drive 10 mA cm −2 in overall water splitting. The electrocatalytic performance shows negligible degradation after long-term durability test for 70 h at 10 mA cm −2 .